2015
DOI: 10.1111/isqu.12196
|View full text |Cite
|
Sign up to set email alerts
|

Roving Bandits? The Geographical Evolution of African Armed Conflicts

Abstract: The fighting in some civil wars primarily takes place in a few stable locations, while the fighting in others moves substantially. We posit that rebel groups that do not primarily fight for a specific ethnic group, that receive outside military assistance, or that have relatively weak fighting capacity tend to fight in inconsistent locations. We develop new measures of conflict zone movement to test our hypotheses, based on shifts in the conflict polygons derived from the new Georeferenced Event Dataset (GED) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 50 publications
(61 reference statements)
0
42
0
Order By: Relevance
“…The degree to which conflicts move will thus depend on the relative strength of the combatants and the potential of the rebel groups for the establishment of legitimate authority over certain pockets of the local population. Earlier work confirms that conflict zones are more mobile when rebel groups are relatively much weaker than government forces and when rebel groups do not claim to be fighting for control over an ethnic homeland (Beardsley, Gleditsch, and Lo, forthcoming). This earlier work, however, does not consider the potential role that third parties can play in shaping these incentives for battles to occur in different locations.…”
Section: Theorymentioning
confidence: 88%
See 2 more Smart Citations
“…The degree to which conflicts move will thus depend on the relative strength of the combatants and the potential of the rebel groups for the establishment of legitimate authority over certain pockets of the local population. Earlier work confirms that conflict zones are more mobile when rebel groups are relatively much weaker than government forces and when rebel groups do not claim to be fighting for control over an ethnic homeland (Beardsley, Gleditsch, and Lo, forthcoming). This earlier work, however, does not consider the potential role that third parties can play in shaping these incentives for battles to occur in different locations.…”
Section: Theorymentioning
confidence: 88%
“…We control for factors that are likely associated with the tendency for conflict to spread because it is possible that the UN is more likely to authorize peacekeeping missions to the countries that have a greater need for containment. In addition to relative rebel weakness and rebel aims, our earlier work has shown that outside military support can strongly affect the propensity for conflict zones to move (Beardsley, Gleditsch, and Lo, forthcoming). We thus include a measure of external support from the UCDP External Support data (Högbladh, Pettersson, and Themnér ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each state the population total is calculated using the 2005 estimates from the most recent version of Gridded Population of the World. A number of recent studies have highlighted the salience of ethnicity with regard to conflict Buhaug and Gleditsch (2008); Weidmann (2009); Costalli and Moro (2012); Beardsley et al (2015). Therefore, a measure for ethnic diversity is included in the model based on the polarisation index from Garcia-Montalvo and Reynal-Querol (2005) which is constructed using data from the Georeferencing of Ethnic Groups (GREG) by .…”
Section: Regression Analysismentioning
confidence: 99%
“…This paper is grounded on different streams of literature, and it merges recent findings on the risk of events of organised violence (Sundberg & Melander ; Beardsley et al ), and land‐use issues with specific attention to peri‐urbanisation processes (McGregor et al ; Schneider & Woodcock ; Ravetz et al ) and large‐scale land acquisitions (DeSchutter ; Deininger ; Cotula ). Based on spatially disaggregated data which allow controlling for local characteristics, the analysis explores whether rising competing interests over land are systematically associated with events of organised violence in Sub‐Saharan Africa within the period 2000–2014.…”
Section: Introductionmentioning
confidence: 99%